2020
DOI: 10.1002/smll.202004575
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Geometry and Flow Through Bacterial Bridges on Patterned Lubricant‐Infused Surfaces (pLIS)

Abstract: Gram-negative bacteria such as Acinetobacter spp., Pseudomonas aeruginosa (P. aeruginosa), Escherichia coli (E. coli), Enterobacter spp. are widely spread in natural and artificial environments. [1] The facultative pathogenic P. aeruginosa is a major cause of chronic infections strongly involved in cystic fibrosis patients Spatial control of bacteria and biofilms on surfaces is necessary to understand the biofilm formation and the social interactions between bacterial communities, which could provide useful hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A similar minimal width of 100 nm was reported in order to avoid adsorption of antimicrobials to channel walls upon diffusion-controlled penetration of an antimicrobial in an infectious biofilm (Ju et al 2020). However, intra-colony channels with much larger diameters of around 10 mm have also been described in E. coli, using giant objective lens microscopy with a high numerical aperture at low magnification ("mesoscopy") (Rooney et al 2020) and even wider channels (18-99 mm) have been described in P. aeruginosa (Lei et al 2020). Collectively, it can thus be concluded that biofilm channels effective for transport processes must have a minimal width of around 100 nm.…”
Section: Structure Of Water-filled Regions In Biofilms: Channels and Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar minimal width of 100 nm was reported in order to avoid adsorption of antimicrobials to channel walls upon diffusion-controlled penetration of an antimicrobial in an infectious biofilm (Ju et al 2020). However, intra-colony channels with much larger diameters of around 10 mm have also been described in E. coli, using giant objective lens microscopy with a high numerical aperture at low magnification ("mesoscopy") (Rooney et al 2020) and even wider channels (18-99 mm) have been described in P. aeruginosa (Lei et al 2020). Collectively, it can thus be concluded that biofilm channels effective for transport processes must have a minimal width of around 100 nm.…”
Section: Structure Of Water-filled Regions In Biofilms: Channels and Poresmentioning
confidence: 99%
“…This corresponds with visualised channel lengths in V. cholerae (Fern andez-Delgado et al 2016), S. mutans (Galbiatti de Carvalho et al 2012), B. subtilis (Wilking et al 2013) and phototrophic (Phoenix and Holmes 2008) biofilms and three species biofilms of P. aeruginosa, Pseudomonas fluorescens and Klebsiella pneumoniae biofilm (De Beer and Stoodley 1995;Stewart 2012). In biofilms of P. aeruginosa, channels have been described with a length of around 700 mm, bridging the distance between two places in a biofilm, but these channels had an extremely wide range of widths (Lei et al 2020). Accepting a minimal length of 1 lm and a width of 100 nm as a characteristic of a channel, channels can be distinguished from pores by a length/width ratio > 10, while pores should have a length to width ratio closer to one.…”
Section: Structure Of Water-filled Regions In Biofilms: Channels and Poresmentioning
confidence: 99%
“…Under this flow, stick-slip dynamics explains the microscopic receding line wherein the contact line remains pinned, as in a "stick" mode, at a specific point on the micropost before detaching into slip mode to move to the next micropost (Yang et al, 2018). Here, the filamentous hornlike structures at the top layer of micropost would be a result of stuck the dimensions, directions, numbers, and positions of bridges (Drescher et al, 2013;Jahed et al, 2017;Lei et al, 2019;Lei et al, 2020;Rusconi et al, 2010;Valiei et al, 2012). shear on E. coli O157:H7 microcolonization using wild-type and isogenic mutant E. coli O157:H7 strains lacking adhesin and adherencemeditating components, or new platforms simulating more complicated but more realistic leaf surfaces (i.e., surface patterns, mechanical properties, and chemical compositions).…”
Section: Discussionmentioning
confidence: 99%
“…As such, leafy green-mimicking substrates have been applied as platforms for a mechanistic understanding of the biofilm formations of various types of cells and a demonstration of the distinguishing plant surface characteristics, including superhydrophobicity and self-cleaning properties. Furthermore, characterization of extracellular matrix from biofilm and their development to filamentous structures, referred to biofilm streamers, have been demonstrated using various approaches including surface modification (i.e., topographical and chemical modifications), flow conditions, bacterial strains, and nutrition availability (Drescher et al, 2013;Jahed et al, 2017;Lei et al, 2019Lei et al, , 2020Rusconi et al, 2010;Valiei et al, 2012). While the interactions between biofilm structures and fluid flow are important, there is still little information regarding the emergence of microcolonies in growing biofilms which may potentially lead to cross-contamination events on fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…For example, micropatterned hydrophilic patches on hydrophobic or slippery surfaces could be employed as biomimetic water-harvesting materials from fog. [21][22][23] The patterned surfaces with defined surface properties also enabled the manipulation of arrays of microdroplets or cells for high-throughput studies, [24][25][26][27] as well as the control on directional transport of droplets to work as surface-tension-confined microfluidic devices without the need for microchannels. [28][29][30] In addition, patterning of surface wettability or chemical reactivity are essential in various sensor systems based on biomolecular immobilization, photonic crystals, or plasmonic nanostructures, in which the assembly of molecules or nanoparticles could be selectively guided into desired positions by the micropatterns.…”
Section: Introductionmentioning
confidence: 99%